2007
DOI: 10.1093/ps/86.8.1662
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Effects of Lactic Acid Bacteria Probiotic Culture on Salmonella in Neonatal Broilers

Abstract: We evaluated the ability of a commercially available lactic acid bacteria-based probiotic culture (LAB) to reduce Salmonella Enteritidis or Salmonella Typhimurium in day-of-hatch broiler chicks. In these experiments, chicks were challenged with Salmonella Enteritidis or Salmonella Typhimurium and treated with LAB 1-h postchallenge. Following treatment, cecal tonsils and ceca were aseptically collected for Salmonella Enteritidis or Salmonella Typhimurium enrichment or Salmonella Enteritidis enumeration, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(67 citation statements)
references
References 18 publications
3
59
0
5
Order By: Relevance
“…Hence, the early administration of 'good' bacteria for competitive exclusion has been proposed as a method to prevent undesirable infections. There are several reports on the capacity of live bacterial cultures (Callaway et al, 2008;Corrier et al, 1998;Nisbet et al,1998;Wagner et al, 2003) and probiotic organisms (Higgins et al, 2007;Higgins et al, 2008;Higgins et al, 2010;Patterson & Burkholder, 2003;Vicente et al, 2008) to reduce the colonization of the gastrointestinal tract of poultry by opportunistic pathogens. The current study showed that the dietary inclusion of Bacillus subtilis enhanced the birds' immunity against Newcastle disease and avian influenza.…”
Section: Assessment Of a Probiotic Containing Bacillus Subtilis On Thmentioning
confidence: 99%
“…Hence, the early administration of 'good' bacteria for competitive exclusion has been proposed as a method to prevent undesirable infections. There are several reports on the capacity of live bacterial cultures (Callaway et al, 2008;Corrier et al, 1998;Nisbet et al,1998;Wagner et al, 2003) and probiotic organisms (Higgins et al, 2007;Higgins et al, 2008;Higgins et al, 2010;Patterson & Burkholder, 2003;Vicente et al, 2008) to reduce the colonization of the gastrointestinal tract of poultry by opportunistic pathogens. The current study showed that the dietary inclusion of Bacillus subtilis enhanced the birds' immunity against Newcastle disease and avian influenza.…”
Section: Assessment Of a Probiotic Containing Bacillus Subtilis On Thmentioning
confidence: 99%
“…Tellez et al evaluated methods to select for individual enteric bacteria capable of inhibiting Salmonella growth in vitro and the ability of selected oxygen tolerant bacteria, in combination, to protect neonatal poults from Salmonella infection following challenge [24,65,66]. Concurrently, they also worked toward the isolation, selection, further evaluation and combination of LAB to control additional foodborne pathogens.…”
Section: Probiotics In Poultry Researchmentioning
confidence: 99%
“…Using a Salmonella challenge model, an effective LAB probiotic, administered 2 hours after Salmonella challenge, had no effect during the first 12 hours on increasing cecal colonization by this pathogen, although marked and rapid decreases were observed between 12 and 24 hours post-challenge [65,76]. Later, using the same model and microarray analysis of gut mRNA expression, gene expression differences in birds treated with a Lactobacillus-based probiotic were compared to saline treated birds.…”
Section: Probiotics In Poultry Researchmentioning
confidence: 99%
“…The lactic acid is a strong prebiotic, which, by lowering the pH to 5.0-6.8 in individual sections of the digestive system, creates favourable conditions for the colonization of useful bacteria as well as aids the resorption of mineral components. As indicated by the research conducted by Byrd et al (2001) and Higgins et al (2007), the addition of lactic acid in drinking water significantly reduces the growth of Salmonella enteritidis and S. typhimurium in the digestive system and lowers their contents in the excreted uric acid.…”
Section: Introductionmentioning
confidence: 99%